Supervisi Klinis dalam Peningkatan Kompetensi Profesionalisme Guru - Sunardi, Sunardi; Satori, Satori (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
Enhancing teachers' professional competence is a key factor in improving the quality of education. One effort to achieve this goal is through clinical supervision. Clinical supervision is a systematic and collaborative approach that involves the observation, evaluation, and coaching of teachers' teaching practices. This method aims to help teachers identify their strengths and weaknesses and provide the necessary guidance for continuous improvement. This research employs a qualitative descriptive method with a case study approach. Data were collected through direct observations, in-depth interviews with teachers and supervisors, and the analysis of relevant documents. The research subjects consisted of junior high school teachers who had received clinical supervision for one semester. The data analysis was conducted using triangulation techniques to ensure the validity and reliability of the findings. The results of the study show that clinical supervision has a positive impact on enhancing teachers' professional competence. Teachers who received clinical supervision demonstrated improvements in lesson planning, the implementation of the teaching-learning process, and the evaluation and reflection of learning activities. Moreover, the collaborative relationship between teachers and supervisors also provides additional motivation for teachers to continuously develop their professional skills. These findings indicate that clinical supervision can be an effective strategy for improving the quality of education through the development of teachers' professionalism